Generation of Maximally Correlated States of (D ? D)-Dimensional Systems in the Absence of Entanglement - Retamal-Abarzua, J; Lopez-Cabrera, C; Allende-Prieto, S; Albarran-Arriagada, F (Institute of Physics Publishing, 2017)
We study the generation of maximally correlated states of (d ⊗ d)-dimensional quantum systems in the absence of quantum entanglement. We found that this class of states can be generated under the assistance of a collective dissipative dynamics. Maximally correlated bipartite states without entanglement, requires maximal entanglement to a third party. We study a bipartite system evolving into a maximally correlated state, without entanglement, when interacting with a finite environment. Copyright © EPLA, 2017.